Bitch doctrine : essays for dissenting adults - Penny, Laurie (Bloomsbury, 2017)
"Smart and provocative, witty and uncompromising, this collection of Laurie Penny's celebrated essays establishes her as one of the most important and vibrant political voices of our time. Bitch Doctrine takes an unflinching look at the definitive issues of our age, from the shock of Donald Trump's election and the victories of the far right to online harassment and the transgender rights movement"--Amazon.